2012
DOI: 10.1371/journal.pone.0040569
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Increases Vulnerability to Aβ42 Toxicity in Drosophila

Abstract: Age is the major risk factor for many neurodegenerative diseases, including Alzheimer's Disease (AD), for reasons that are not clear. The association could indicate that the duration or degree of exposure to toxic proteins is important for pathology, or that age itself increases susceptibility to protein toxicity. Using an inducible Drosophila model of AD, we investigated these possibilities by varying the expression of an Aβ42 transgene in neurons at different adult ages and measuring the effects on Aβ42 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…However, we have observed both soluble and insoluble Aβ in the Arctic Aβ42 flies [(Rogers et al, 2012), and data not shown]; and the ability of lithium to reduce translation of the Aβ peptide without affecting its clearance may lower the level of soluble Aβ. In a wider context, lithium might be beneficial in ameliorating toxicity of AD by lowering expression of APP and of proteins that are involved in the generation of Aβ from APP.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, we have observed both soluble and insoluble Aβ in the Arctic Aβ42 flies [(Rogers et al, 2012), and data not shown]; and the ability of lithium to reduce translation of the Aβ peptide without affecting its clearance may lower the level of soluble Aβ. In a wider context, lithium might be beneficial in ameliorating toxicity of AD by lowering expression of APP and of proteins that are involved in the generation of Aβ from APP.…”
Section: Discussionmentioning
confidence: 79%
“…Chymotrypsin-like peptidase activity of the proteasome was assayed the using fluorogenic peptide substrate Succinyl-Leu-Leu-Val-Tyr-amidomethylcoumarin (LLVY-AMC), based on a previously published protocol (Bulteau et al, 2002; Rogers et al, 2012). 20 μg of crude fly head homogenate total protein was incubated at 37°C with 25 μM LLVY-AMC in a final volume of 200 μLs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a reduction in proteasome activity and abundance has also been demonstrated in day 20e30 Drosophila heads and is associated with the impaired assembly of the 20S proteasome and the 19S regulatory subunits (Tonoki et al, 2009). A 50% reduction in proteasomal activity has also been detected between days 9 and 27 in Drosophila heads, when measured by a fluorogenic peptide substrate (Rogers et al, 2012). In addition, another study showed reduced proteasomal activity in the spinal cord of rats at 12, 24, and 28 months of age compared with spinal cord from younger animals (Keller, Huang, & Markesbery, 2000), suggesting that a relatively early decline in proteasomal activity is an evolutionary conserved feature of aging.…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 93%